Hosoya Index, Lucas Numbers and QSPR - McLaughlin, Kevin; Dawson, Kevin; Westerberg, Tina (My University, 2005)
The number of different molecules with the formula C64H130 is more than one hundred million billion times greater that the number of different molecules of all types and formulas cataloged in all of human history. Therefore, it is imperative that theoretical chemists develop methods to predict properties of molecules from their structures so that synthetic chemists can identify on which of the enumerable molecular structures they should expend their finite resources. One such approach to predicting the properties of molecules involves something called a topological index. We present an analysis of the problems involved in the use of one such topological index for quantitative structure-property relationships.
Color poster with text detailing research conducted by Kevin Dawson and Tina Westerberg, advised by Dr. Kevin McLaughlin (University of Wisconsin-River Falls) that examines the use of a topological index to predict the properties of molecules.
Keywords: Boiling-Points; QSPR; Chemistry; Lucas Numbers; Topological Index; Hosoya Index; Quantitative Structure-Property Relationships; Molecular Structure